Benefits of traditional and local ecological knowledge for species recovery when scientific inference is limited - Sheppard, Donna J.; Stark, Danica J.; Muturi, Solomon Wachiuri; Munene, Peter Hannington (Frontiers in Conservation Science, 2024)
Many critically endangered species persist in remnant populations so small that ecological information required to assist recovery, such as species-typical demographic parameters and habitat preferences, can be difficult to acquire based on science alone. Traditional ecological knowledge (TEK) or local ecological knowledge (LEK) can fill information gaps and provide additional understanding, though this expertise is not everlasting and often overlooked. We report on research focused on a species survival plan for mountain bongo (Tragelaphus eurycerus isaaci), a critically endangered antelope endemic to Kenya, persisting in the wild with fewer than 80 individuals in four separated montane forests. In preparation for a potential conservation translocation of captive-bred bongos into one or more forests, extensive camera trapping yielded limited results, suggesting that data were based on the activities of just a few individuals. Moreover, additional information critical to translocations, such as typical group size and sex ratios, could neither be observed nor obtained from the literature. This knowledge gap was largely resolved using expert interviews conducted with eight former Kenyan hunters, along with historical range and browse mapping, enriching understanding of behavioral characteristics rendering bongo particularly vulnerable to exploitation. Consistently similar responses from observations spanning a 50-year period (1950s to 1990s) across four ecosystems added certainty to responses. This study endorses a combination of data sources when dealing with remnant populations, and specifically recommends making use of this documented mountain bongo TEK/LEK to inform decisions about potential bongo reintroductions in Kenya.